Gastric Outlet Obstruction due to Intramural Duodenal Hematoma after Endoscopic Biopsy: Possible Therapeutic Role of Endoscopic Dilation - Samra, Mahmud (Case Rep Gastroenterol, 2018)
Intramural duodenal hematoma (IDH) is an extremely rare complication after endoscopic biopsy. It typically presents with symptoms due to duodenal obstruction, which include abdominal pain and bilious vomiting. The hematoma may also expand and cause ampullary compression leading to pancreatitis and cholestasis. Computed tomography scan and abdominal ultrasound are the most common diagnostic modalities. Treatment is usually conservative, with bowel rest, nasogastric suctioning and total parenteral nutrition. Refractory cases have been described, requiring endoscopic therapy or surgical drainage. We describe a 28-year-old healthy male who presented with acute abdominal pain a few hours after a routine esophagogastrodudenoscopy with biopsies was performed. Following an otherwise uneventful endoscopy, he developed a gastric outlet obstruction and pancreatitis secondary to an IDH. The patient was managed conservatively. Resolution of his gastric outlet obstruction occurred immediately after gentle passage of the endoscope through the narrowed duodenal lumen.